(untitled) (Revista Educação, Artes e Inclusão, 2023)
Discussing new possibilities of theatre and processes might be a way to figure out the possible understanding that such themes reach currently, considering new pedagogical processes when it comes to school issues. For that matter, we present a provocation to the concept that presence happens by listening to one another. As a reference point, we can mention the experience we had from our master’s degree, which involved Young people between 13 and 17 years old in a public school in the city of Natal, RN, Brazil by applying the method of pedagogical workshop and improvisation games. This has enabled us to move forward in experimenting a process that looks to broaden the concept of face-to-face theatre, by transposing the theatrical scene, having the sound as scenic unfolding. That way, a convergence game and the differences between presence (theatrical scene) and absence (sound scene) are established. The outcome has allowed us to assess the expansion of the scenic process happened by revealing new ways to understand himself and oneself, in addition to provoke the experience that by receiving something from the audible matrix might expand the comprehension of the scenic presence and, in the case of this study, of the very idea of inclusion.